Ways of formation of Kazakhstan’s patriotism in the course of Public Service and its legal basis - Ramashov, O.N.; Мussin К.S.; Lavnichak А. (Bulletin of the Karaganda University “Law Series”, 2021)
This article discusses the legal foundations of the formation of Kazakhstan’s patriotism in the course of Public Service in the country. The authors point out that patriotism in Kazakhstan is a respectful, humane and friendly attitude of peoples, which has always been characteristic of Kazakhstanis, as well as calling all Kazakhstanis to creative work, to make every effort to preserve peace, unity and independence of our country, creating conditions for the development of education, culture, economy, social sphere in the state of Kazakhstan. In the course of the implementation of the national policy of the country within the framework of the new Kazakhstan patriotism it is assumed that it accounts for the equality of all nationalities, races, confessions in the need to make coordinated decisions, taking into account the interests of different peoples living on the territory of Kazakhstan. The authors analyze the fact that Kazakhstan’s patriotism is one of the constitutional ideas reviving it as a common national idea of love for the motherland, as well as respect for its history. The rights of citizens in the Republic of Kazakhstan are provided by the Constitution and norms of the law, ensure their equality before the law, regardless of their social status, ethnicity, official career or other origin, religious affiliation and other differences. In this context the authors note that in the formation of domestic patriotism in the course of public service every citizen of Kazakhstan has the opportunity to contribute to the development of language, traditions, culture, and, in general, all institutions of the state should work to ensure equality of opportunities.